2012
DOI: 10.1590/s0102-33062012000100010
|View full text |Cite
|
Sign up to set email alerts
|

Frugivoria por aves em um mosaico de Floresta Estacional Semidecidual e reflorestamento misto em Rio Claro, São Paulo, Brasil

Abstract: Frugivoria por aves em um mosaico de Floresta Estacional Semidecidual e refl orestamento misto em Rio Claro, São Paulo, Brasil RESUMO (Frugivoria por aves em um mosaico de Floresta Estacional Semidecidual e reflorestamento misto em Rio Claro, São Paulo, Brasil). Visando subsidiar futuros projetos de recuperação florestal com base nas interações animal--planta, foram avaliadas as espécies ornitocóricas e o consumo de frutos por aves em um mosaico de Floresta Estacional Semidecidual e um reflorestamento misto, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
1
9
0
4
Order By: Relevance
“…Similar results were obtained by Athiê and Dias (2012) in a study of frugivory by birds in a reforestation area in Rio Claro, São Paulo State. The authors found that the species with the highest visitation rates and consumption by birds was the exotic Melia azedarach L. (Meliaceae), which produced fruits during all dry season, as well as C. reevesii.…”
Section: Seed Depositionsupporting
confidence: 87%
“…Similar results were obtained by Athiê and Dias (2012) in a study of frugivory by birds in a reforestation area in Rio Claro, São Paulo State. The authors found that the species with the highest visitation rates and consumption by birds was the exotic Melia azedarach L. (Meliaceae), which produced fruits during all dry season, as well as C. reevesii.…”
Section: Seed Depositionsupporting
confidence: 87%
“…Espécies que produzem frutos pequenos e em grandes quantidade são classificadas na literatura como generalistas (Howe & Estabrook, 1977), atraindo uma ampla variedade de espécies de aves, muitas das quais empregam frutos em sua dieta apenas ocasionalmente (Fleming et al, 1987;Francisco & Galetti, 2002;Athiê & Dias, 2012). Tal fato poderia explicar o baixo consumo de frutos pelas demais espécies de aves observadas neste estudo.…”
Section: Discussionunclassified
“…Among the most abundant species, only T. melancholicus is an effective disperser, ingesting fruits from forest edges and depositing the seeds in open environments (Fonseca & Antunes 2007, Athiê & Dias 2012. Other dominant species (including C. talpacoti, L. cucullatus, Zenaida auriculata and Volatinia jacarina) are granivorous and feed on seeds of Poaceae and Asteraceae (Belton 1985, Azpiroz et al 2012, which are abundant in the area.…”
Section: Discussionmentioning
confidence: 99%